In vitro assessment of the probiotic potential of lactobacilli isolated from Minas artisanal cheese produced in the Araxá region, Minas Gerais state, Brazil - Silva, J.G.; Castro, R.D.; Sant’Anna, F.M.; Barquete, R.M.; Oliveira, L.G.; Acurcio, L.B.; Luiz, L.M.P.; Sales, G.A.; Nicoli, J.R.; Souza, M.R. (Arquivo brasileiro de medicina veterinária e zootecnia, 2019)
ABSTRACT Minas artisanal cheese is made from endogenous starter cultures, including lactic acid bacteria (LAB). Some LAB may possess probiotic potential. Thus, this study aimed to evaluate the in vitro probiotic properties of lactobacilli isolated from Minas artisanal cheeses produced in Minas Gerais. Ten samples of lactobacilli, formerly isolated from those cheeses, were submitted to the following assays: antimicrobial susceptibility, tolerance to artificial gastric juice and biliary salts, production of hydrogen peroxide and antagonism against pathogenic and non-pathogenic micro-organisms. Only L. plantarum (C0) was sensitive to all tested antimicrobials, while the other LAB samples were resistant to at least one drug. Six samples were tolerant to artificial gastric juice, and L. brevis (A6) even grew in that medium. Three samples were tolerant to biliary salts. Only L. brevis (E35) produced hydrogen peroxide. Difference (P< 0.05) was observed among the means of inhibition haloes of lactobacilli against Enterococcus faecalis ATCC 19433 and Lactobacillus plantarum C24 in spot-on-the-lawn assay. All samples of lactobacilli inhibited Escherichia coli ATCC 25922, Salmonella enterica var. Typhimurium ATCC 14028 in co-culture antagonism test (P< 0.0001). Most lactobacilli samples showed in vitro probiotic potential. From the tested samples, L. brevis (A6) presented the best results considering all in vitro probiotic tests. RESUMO O queijo minas artesanal é produzido por culturas starters endógenas, incluindo bactérias ácido-láticas (BAL). Algumas BAL podem possuir potencial probiótico. Com isso, este estudo teve como objetivo avaliar as propriedades probióticas in vitro de lactobacilos isolados de queijo minas artesanal produzido no estado de Minas Gerais. Dez amostras de lactobacilos, previamente isoladas desses queijos, foram submetidas aos seguintes testes: susceptibilidade aos antimicrobianos, tolerância ao suco gástrico artificial e aos sais biliares, produção de peróxido de hidrogênio e antagonismo contra micro-organismos patogênicos e não patogênicos. Apenas L. plantarum (C0) foi sensível a todos os antimicrobianos testados, enquanto as outras amostras de BAL foram resistentes a, pelo menos, uma droga testada. Seis amostras foram tolerantes ao suco gástrico artificial, e L. brevis (A6) apresentou crescimento nesse meio. Três amostras foram tolerantes aos sais biliares. Apenas L. brevis (E35) produziu peróxido de hidrogênio. Diferença (P<0,05) foi observada entre as médias dos halos de inibição de lactobacilos contra Enterococcus faecalis ATCC 19433 e Lactobacillus plantarum C24 no teste do spot-on-the-lawn. Todas as amostras de lactobacilos inibiram Escherichia coli ATCC 25922, Salmonella enterica var. Typhimurium ATCC 14028 no teste de antagonismo em cocultura (P<0,0001). A maioria das amostras de lactobacilos apresentou potencial probiótico in vitro. Com base nas amostras testadas, L. brevis (A6) apresentou os melhores resultados, considerando-se todos os testes probióticos in vitro.